“We Are Empowered in Our Own Way”: The Symbolization of Empowered Women in the Mamak Peduli Community - Sofia, Diina; Prianti, Desi Dwi (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
This study examines the distinctive communication practices associated with women’s empowerment from an Eastern Perspective, focusing on the Mamak Peduli community in Lamongan, East Java, Indonesia. Unlike Western notions of empowerment, Mamak Peduli community construct and reach consensus on the concept of empowered women with socio-religious characters through communication practice. Employing a qualitative method and procedural ethnography, the study involves direct engagement with the community. Data were collected through participatory observation, in-depth interviews, and documentation, followed by data analysis using an interactive field model based on symbolic interactionism theory. Findings reveal that the community organizes empowerment through structured, agreed-upon group activities, particularly those involving input group communication. The shared understanding of empowerment is represented through the alignment of individual actions with broader social and religious capacities. These activities foster both personal growth and community benefit. Empowerment in Mamak Peduli is symbolized through routine socio-religious practices that are both internal (self-development) and external (community benefit) in nature. These practices collectively symbolize the empowered woman within the local cultural context. The Mamak Peduli community exemplifies how grassroots communication and socio-religious collaboration can construct a unique, culturally embedded model of women’s empowerment that fosters both individual capability and communal well-being. This study presents a culturally grounded framework for women’s empowerment communication that contributes to advancing SDG 5 (Gender Equality) by demonstrating how faith-based and communal practices can foster inclusive participation and relational equity in socio-religious contexts.